How Common Sense Is Exercised and Flawed: Insights of Philosophy of Science - Jonathans, Peggy Magdalena; Tamelan, Thersia Magdalena (Journal of Language, Education, Literature, and Culture, 2025)
Among the laypeople, public speakers are thought to represent the institution they are affiliated with or to characterize their identity. Laypeople might be amazed by the sound judgment of well-known figures, although they seem to be carried away from scientific justification. Studying the nature of language, its meaning, and its connection to reality (a.k.a philosophy of language) would be relevant to analyzing the depth of the speaking. The present study will disclose the logical fallacy made in the talk of an Indonesian public figure by meticulously observing his videotaped talk on the YouTube platform. The findings show the public figure contrasted the government’s propositions with his wrong inferences, based on the analytical truth in his false common sense, made prudent suggestions and sound judgment without a scientifically tested conclusion, employed lots of metaphors throughout the talk, and tended to overgeneralize. Despite the flaws, his partially true proposition could be argued and served as a mind-blowing reflection and criticism of the Indonesian wall of democracy. The study is worthwhile in correcting the strong claims the speaker highlighted because common sense is prone to play a tricky pragmatic role in thinking about how things can be. As everyone has their innate common sense within the intuitive aspect of knowledge, the knowledge of absolute truth may lead everyone to distinguish right from wrong and decide wisely for a better life for all.